Safety of sodium-glucose transporter 2 (SGLT-2) inhibitors in patients with type 2 diabetes: a meta-analysis of cohort studies - Li, Chun Xing; Liu, Tian Tian; Zhang, Qian; Xie, Qing; Geng, Xu Hua; Man, Chun Xia; Li, Jia Yi; Mao, Xin Ying; Qiao, Yue; Liu, Hua (Frontiers in Pharmacology, 2023)
This study aimed to investigate the association between the use of sodium-glucose transporter 2 inhibitors (SGLT-2i) and the risk of diabetic ketoacidosis (DKA), lower limb amputation (LLA), urinary tract infections (UTI), genital tract infections (GTI), bone fracture, and hypoglycemia in cohort studies.A systematic search was conducted in the PubMed and Embase databases to identify cohort studies comparing the safety of SGLT-2i versus other glucose-lowering drugs (oGLD) in patients with type 2 diabetes mellitus (T2DM). The quality of the studies was assessed using the Newcastle-Ottawa Scale.Primary endpoints were DKA and LLA, while secondary endpoints included UTI, GTI, bone fracture, and hypoglycemia. Hazard ratios (HR) with 95% confidence intervals (CI) were calculated.A total of 9,911,454 patients from 40 cohort studies were included in the analysis. SGLT-2i use was associated with a higher risk of DKA (HR: 1.21, 95% CI: 1.07-1.37, p = 0.003) and GTI (HR: 2.72, 95% CI: 2.48-2.98, p < 0.01). However, it was not associated with an increased risk of LLA (HR: 1.06, 95% CI: 0.92-1.23, p = 0.42), UTI (HR: 0.99, 95% CI: 0.89-1.10, p = 0.83), or bone fracture (HR: 0.99, 95% CI: 0.94-1.04, p = 0.66). Furthermore, SGLT-2i was associated with a reduced risk of hypoglycemia. Furthermore, compared to dipeptidyl peptidase 4 inhibitors, SGLT-2i as a class and individually was associated with an increased risk of DKA. Canagliflozin specifically increased the risk of LLA (HR: 1.19, 95% CI: 1.04-1.36, p = 0.01). The subgroup analysis suggested that SGLT-2i increased the risk of LLA among patients with a history of cardiovascular disease.SGLT-2i versus oGLD was associated with a similar occurrence of LLA, UTI, and bone fracture. However, SGLT-2i was associated with a higher risk of DKA and GTI than oGLD. These findings provide valuable information on the safety profile of SGLT-2i in patients with T2DM and can help inform clinical decision-making.